Pengaruh Penggunaan Wordwall terhadap Peningkatan Motivasi Belajar Qur’an Hadis Siswa Kelas VII MTs N 3 Banyumas - Annisa Marwa Istihgfarani; Harisatunnisa Harisatunnisa (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the effectiveness of using Wordwall as a learning medium in enhancing students’ learning motivation in the Qur’an and Hadith subject for Grade VII at MTs N 3 Banyumas. The research background is rooted in the low learning motivation of students, as indicated by limited active participation, low questioning initiative, and signs of learning fatigue resulting from the dominance of conventional teaching methods. A quantitative approach was employed using a pre-experimental one–group pretest–posttest design. The study involved Grade VII H students selected through purposive sampling. Data were collected using a Likert-scale learning motivation questionnaire and analyzed through validity and reliability testing, followed by inferential statistical analysis to determine the effect of the intervention. The findings demonstrate that the use of Wordwall has a positive and significant impact on improving students’ learning motivation. The interactive features and gamification elements of Wordwall effectively increase students’ attention, engagement and create a more enjoyable learning atmosphere. Overall, Wordwall is considered an effective and innovative learning medium for boosting learning motivation in the Qur’an Hadith subject at MTs N 3 Banyumas. Keywords: Wordwall, learning motivation, Qur’an Hadith learning, interactive media, gamification.